2012
DOI: 10.4269/ajtmh.2012.11-0237
|View full text |Cite
|
Sign up to set email alerts
|

Differential Pattern of Infection of Sylvatic Nymphs and Domiciliary Adults of Triatoma infestans with Trypanosoma cruzi Genotypes in Chile

Abstract: Abstract. In Chile, the main vector of Chagas disease, Triatoma infestans, is under control after insecticide spraying. However, it has been found colonizing wild habitats. This study evaluated Trypanosoma cruzi infection of sylvatic and domiciliary T. infestans and identified their parasite genotypes. The sample studied was composed mainly of T. infestans sylvatic nymphs and domiciliary adults from a semi-urban area with human dwellings under vector control surveillance. Results showed prevalences of 57.7% in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 55 publications
2
12
0
1
Order By: Relevance
“…In the present study a large number of mixed infections in humans (TcV plus another DTU) were found in the less endemic arid areas of Norte Grande (XV, I and II regions), with levels of mixed infections similar to the most endemic ones (III, IV, and V regions). The T. cruzi DTUs composition in T. infestans (mainly TcI) also presented a very homogeneous distribution all over the studied area, as previously described [Bacigalupo et al, 2012]. Interestingly, unknown genotypes were not as frequent as in human patients.…”
Section: Discussionsupporting
confidence: 78%
“…In the present study a large number of mixed infections in humans (TcV plus another DTU) were found in the less endemic arid areas of Norte Grande (XV, I and II regions), with levels of mixed infections similar to the most endemic ones (III, IV, and V regions). The T. cruzi DTUs composition in T. infestans (mainly TcI) also presented a very homogeneous distribution all over the studied area, as previously described [Bacigalupo et al, 2012]. Interestingly, unknown genotypes were not as frequent as in human patients.…”
Section: Discussionsupporting
confidence: 78%
“…High T . cruzi infection rates (>50%) of triatomines in urban areas were also observed in Chile [ 31 ] and Bolivia [ 6 ]. The high prevalence of T .…”
Section: Discussionmentioning
confidence: 90%
“…Trypanosoma cruzi identification and lineage typing followed previously described PCR protocols [ 29 ]. We used specific primers from previous publications [ 30 , 31 ] and new primers developed in this study to evaluate triatomine blood meals ( Table 1 ). The list of animals investigated as probable food sources for triatomines are shown in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
“…Only TcII and TcVI have been found in M. gajardoi in Chile [66,67], TcI and TcII in M. spinolai [66] and subsequently TcI, TcII, TcV, and TcVI [68], while in T. infestans, the most important [69].…”
Section: Trypanosoma Cruzi Lineagesmentioning
confidence: 99%